Kelemahan Administratif sebagai Penyebab Rendahnya Kepatuhan Indonesia terhadap UNESCO World Heritage Convention dalam Pelaksanaan Konservasi Borobudur - Elmira, Nabilah Rifdha; Wahyudi, Fendy Eko (Journal of International Relations, 2020)
This research is based on the findings that there are non-compliances to the UNESCO 1972 Convention Concerning the Protection of World Cultural and Natural Heritage occurring in Borobudur Temple Compounds conservation practice. The non-compliances are evident as the UNESCO had issued two Reactive Monitorings and seven State of Conservation reports consisting of evaluations and recommendations following the non-compliances. Using Ronald B. Mitchell’s Compliance Theory, this research aims to find the cause of noncompliances occurring in Borobudur Temple Compounds conservation practice. Stakeholder Power and Interest Matrix and Actor-Linkage Matrices are used in order to find the primary actors having the biggest influences in the conservation practice.